Feasibility Analysis for Opening a New Branch of Bank Syariah Indonesia in Lawe Alas Subdistrict, Southeast Aceh Regency - Asrah, Bengi; Kamila, Kamila; Nurwani, Nurwani (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study examines the feasibility of establishing a new Bank Syariah Indonesia (BSI) outlet in the Lawe Alas District, Southeast Aceh, employing a qualitative case study approach that incorporates interviews and observations. Although the economic potential in the agriculture, small trade, and service sectors is considerable, the level of Islamic financial literacy among the community remains low. Financial transactions are predominantly cash-based, and limitations in digital infrastructure pose significant obstacles. The research findings indicate that while demand for Islamic financial services is increasing, the transaction rate has only reached 40% of the population, requiring careful consideration before expansion. This study recommends opening a new outlet, accompanied by efforts to enhance digital literacy, strengthen BSI Link services, and optimize network infrastructure to accelerate Islamic financial inclusion in the region.